Anticonvulsant treatment of asphyxiated newborns under hypothermia with lidocaine: efficacy, safety and dosing. Issue 4 (8th January 2013) - van den Broek, Marcel P H; Rademaker, Carin M A; van Straaten, Henrica L M; Huitema, Alwin D R; Toet, Mona C; de Vries, Linda S; Egberts, Antoine C G; Groenendaal, Floris
Abstract : Background: Lidocaine is an antiarrythmicum used as an anticonvulsant for neonatal seizures, also during therpeutic hypothermia following (perinatal) asphyxia. Hypothermia may affect the efficacy, safety and dosing of lidocaine in these patients. Objective: To study the efficacy and safety of lidocaine in newborns with perinatal asphyxia during moderate hypothermia, and to develop an effective and safe dosing regimen. Methods: Hypothermic newborns with perinatal asphyxia and lidocaine for seizure control were included. Efficacy was studied using continuous amplitude-integrated electroencephalography. Safety was assessed using continuous cardiac monitoring. An optimal dosing regimen was developed with simulations using data from a pharmacokinetic model. Plasma samples were collected during hypothermia on consecutive mornings. Results: A total of 22 hypothermic and 26 historical normothermic asphyxiated newborns with lidocaine were included. A response of 91% on epileptiform activity on the amplitude-integrated EEG was observed for lidocaine add-on therapy. No relationship between lidocaine or MEGX plasma concentrations and heart frequency could be identified. None of the newborns experienced cardiac arrythmias. Hypothermia reduced lidocaine clearance by 24% compared with normothermia. A novel dosing regimen was developed an initial bolus loading dose of 2 mg/kg, for patients with body weight 2.0–2.5 kg followed by consecutive continuous infusions of 6 mg/kg/h (for 3.5 h), 3 mg/kg/h (for 12 h), 1.5 mg/kg/h (for 12 h), or for patients with bodyweights 2.5–4.5 kg 7 mg/kg/h (for 3.5 h), 3.5 mg/kg/h (for 12 h), 1.75 mg/kg/h (for 12 h), before stopping. Conclusions: Lidocaine can be assumed to be an effective antiepileptic drug during hypothermia in asphyxiated neonates.